2010
DOI: 10.1007/s00383-010-2612-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy complications in infants and children: a comparative study

Abstract: The inadvertent formation of a gastrocolic fistula was avoided with the use of laparoscopy to aid PEG insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 5 publications
4
12
0
1
Order By: Relevance
“…Another support of LAG prior PEG regarding complications has also been shown in a previous review of complications after gastrostomy placements [23] and a recent meta-analysis with fewer studies [24]. …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Another support of LAG prior PEG regarding complications has also been shown in a previous review of complications after gastrostomy placements [23] and a recent meta-analysis with fewer studies [24]. …”
Section: Discussionmentioning
confidence: 69%
“…For example, the creation of pneumoperitoneum during laparoscopic surgery may be unsafe in some patients with underlying respiratory disease. In addition, a history of prior upper abdominal surgery may complicate the operative course [23]. …”
Section: Discussionmentioning
confidence: 99%
“…The mean age at G-tube insertion in this group with PRS was 66 days (range 7-167 days, median 60 days) and mean weight 4.27 kg (range 1-7 kg, median 4.3 kg) compared to a mean age 3.9 years (range 1 day-23 years, median 1.53 years) and weight 13.4 kg (range 1-77 kg, median 8.6 kg) of our total population referred for a G-tube at this institution (unpublished data). This patient population is also younger and smaller than the mean age and weight of other pediatric reports in the literature [22][23][24][25][26]. Despite these demographics, the high technical success rate of radiologically placed G-tube insertions in this study (100%) is similar to that found in a meta-analysis by Wollman et al [27] of 99.2% for radiologically placed G-tubes, and compares well to the rate of 95% for PEG and 98.5% placed by laparoscopy [23].…”
Section: Discussionmentioning
confidence: 89%
“…1,2 This approach provides visualization of the stomach but not the peritoneal cavity, which can lead to injuries to the colon, small bowel, liver and spleen. [6][7][8][9][10][11] Another disadvantage is that the long PEG tube must be left in place for a few months before it can be exchanged for a skin-level device. This requires additional sedation, general anesthetic, or endoscopic retrieval.…”
Section: Discussionmentioning
confidence: 99%